Teaching History: The Dynamics of Islamic Politics in Andalusia and Its Impact on Civilization Transformation - Efendi, Januari Riki; Panggabean, Ilham Budiman; Mahendra, Yusril Ihza; Harahap, Elly Warnisyah; Nasution, Hasan Bakti (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study examines the historiography of Islamic political dynamics in Andalusia within the context of history education and civilization transformation. It explores the development of Islamic politics from the arrival of Islam in the 8th century to the fall of the Nasrid Kingdom in Granada in the 15th century. Using a qualitative method and historical analysis, the findings show that the political dynamics of Islam in Andalusia were influenced by internal factors, such as dynastic conflicts and power struggles, as well as external factors, such as Christian invasions and cultural interactions with Europe. Furthermore, this study highlights Andalusia’s contributions to knowledge, arts, and culture, which significantly influenced European civilization. These findings emphasize the importance of understanding Andalusia’s political dynamics as part of history education to enrich perspectives on the interaction between Islam and the Western world and its impact on the development of global civilization.